Analisis Pengaruh Penambah Kapur Gypsum Terhadap Indeks Plastisitas Tanah - Jhon Fernando Siagian; Tika Ermita Wulandari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Soil has a very important role in construction, namely in buildings, roads, bridges, dams and other buildings, so soil with adequate technical properties is needed. Work will encounter difficulties if you encounter soil that has large shrinkage characteristics, this causes damage to the building standing on it. To improve the properties of peat soil in the field of civil engineering, soil stabilization is carried out. Soil stabilization is in principle to improve the quality of soil that is not good, or improve the quality of soil that is actually already classified as good. The characteristics of peat soil include: high organic content, easy degradation when exposed to water, and if the soil experiences dryness the soil shrinks. The liquid limit of the original soil was 63.505% and when the lime mixture was added it became 61.46% in a mixture of 5% lime, 53.47% in a mixture of 10% lime, 49.30% in a mixture of 15% lime, and 28.55% in a mixture of lime 20%. The plastic limit of the original soil was 24.03% and when the Gypsum lime mixture was added it became 29.16% in a mixture of 5% lime, 31.11% in a mixture of 10% lime, 34.15% in a mixture of 15% lime, and 36.14% in a 20% lime mixture. As the Plastic Limit value increases and the Liquid Limit value decreases in the soil, the plasticity index of the soil decreases and the cohesive properties of the soil decrease.